Governance and Institutions in Development in Africa - (:unkn) unknown (My University, 2023)
This article establishes the link between governance and institutional quality on economic performance within African economies. The paper establishes whether these social and economic structures support or constrain efforts to achieve sustainable development within these economies. In establishing the link between governance and institutions with development outcomes, the authors use the Worldwide Governance Indicators and OECD`s Country Risk Classifications as two institutional quality and governance measures. The article equally looks at the facets of governance, institutional quality dimensions, and how they impact development outcomes. Consequently, acceleration in economic growth in the African economies shall not only require accountable and transparent governments, but equally strong institutional frameworks and human capacity building alongside visionary leadership with sound policies and their subsequent implementation. The paper proposes strategic interventions toward improving governance and strengthening institutional frameworks for accelerated growth and development.
Keywords: African Research